Bloodtaking and peacemaking : feud, law, and society in Saga Iceland - Miller, William Ian, 1946- (University of Chicago Press, 1990)
Dubbed by the New York Times as "one of the most sought-after legal academics in the county," William Ian Miller presents the arcane worlds of the Old Norse studies in a way sure to attract the interest of a wide range of readers. Bloodtaking and Peacemaking delves beneath the chaos and brutality of the Norse world to discover a complex interplay of ordering and disordering impulses. Miller's unique and engaging readings of ancient Iceland's sagas and extensive legal code reconstruct and illuminate the society that produced them. People in the saga world negotiated a maze of violent